Corticotropin releasing hormone and Urocortin 2 activate inflammatory pathways in cultured trophoblast cell lines. (December 2015) - Novembri, Romina; De Clemente, Caterina; Funghi, Lucia; Torricelli, Michela; Voltolini, Chiara; Challis, John R.; Petraglia, Felice
Abstract: Objective: Embryo implantation and parturition are recognized as inflammatory events involving endocrine and immune system. NF-kB and MAPK are two transcription factor families involved in inflammation. A possible role of neuroendocrine mechanism in early pregnancy and delivery was proposed for the neuropeptides related to corticotropin releasing hormones (CRH), named Urocortins (Ucns). Experimental and clinical studies support a role for CRH, Ucn, Ucn2 and Ucn3 in the endocrine/immune modulation of inflammation in human trophoblast; however the intracellular mechanisms are not yet recognized. The aim of the present study was to evaluate which of these neuropeptides modulate NF-kB or MAPKs pathways. Study design: In Jeg-3 placental cell line the effect of CRH, Ucn, Ucn2 or Ucn3 on NF-kB and MAPKs pathways were evaluated using Western blot analysis. Results: CRH induced the phosphorylation of MAPK subunits; Ucn2 was able to induce the phosphorylation of both NF-kB and MAPK subunits. Ucn and Ucn3 had no effects on these pathways. Conclusions: These data provide novel information on inflammatory process in trophoblast cells: Ucn2 is a potent pro-inflammatory neuropeptide via NF-kB and MAPK pathways and CRH via MAPK, and CRH and Ucn2 network participates in the inflammatory mechanisms of pregnancy and parturition.